Waterfront at Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Shows men, boats and piles of lumber on the beach. Caption on image: "Water fron Nome, Alaska" Original photograph by Eric A. Hegg 1247; copied by Webster and Stevens 173.A.